2014
DOI: 10.1111/pan.12348
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dexmedetomidine on early stage renal functions in pediatric patients undergoing cardiac angiography using non‐ionic contrast media: a double‐blind, randomized clinical trial

Abstract: Dexmedetomidine may be beneficial in protecting against contrast-induced nephropathy during pediatric angiography by preventing the elevation of vasoconstrictor agents such as plasma endothelin-1 and renin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
1
23
0
3
Order By: Relevance
“…The use of dexmedetomidine for the pre vention of AKI of diverse etiologies, including CAAKI, has been championed by a Turkish group. Bayram et al 45) analyzed the effect of dexmedetomidine in a randomized, controlled trial (RCT) involving 60 children with CHD, scheduled for coronary angiography. The authors observed CAAKI (pRIFLE criteria) in 3 patients (10%) in the inter vention arm and in 11 (36.7%) in the control arm.…”
Section: Pharmacologic Strategiesmentioning
confidence: 99%
“…The use of dexmedetomidine for the pre vention of AKI of diverse etiologies, including CAAKI, has been championed by a Turkish group. Bayram et al 45) analyzed the effect of dexmedetomidine in a randomized, controlled trial (RCT) involving 60 children with CHD, scheduled for coronary angiography. The authors observed CAAKI (pRIFLE criteria) in 3 patients (10%) in the inter vention arm and in 11 (36.7%) in the control arm.…”
Section: Pharmacologic Strategiesmentioning
confidence: 99%
“…DEX has potential neuroprotective effects [11], especially on the hypoxia-damaged brain. The use of DEX during paediatric angiography prevents renal damage caused by contrast medium, resulting from limited increases in the levels of vasoconstricting substances, endothelin-1 and rennin [12].Our observations reveal that DEX can be a valuable supplement of sedation with other agents, when their action is insufficient; more importantly, it can replace opioids, when they are no longer needed and there is a risk of a patient's adverse reactions to their withdrawal. Since DEX does not…”
mentioning
confidence: 80%
“…DEX has potential neuroprotective effects [11], especially on the hypoxia-damaged brain. The use of DEX during paediatric angiography prevents renal damage caused by contrast medium, resulting from limited increases in the levels of vasoconstricting substances, endothelin-1 and rennin [12].…”
mentioning
confidence: 99%
“…In addition, the serum creatinine does not accurately depict kidney function until stead-state equilibrium, which can take several days. Neutrophil gelatinase-associated lipocalin (NGAL) in urine and plasma, 2 hr after contrast administration have been shown to be predictive biomarkers of CIN [18] but these results remain unvalidated [19]. Biomarkers such as NGAL could allow for earlier identification and intervention to avoid bad outcomes associated with CIN.…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Clonidine and dexmedetomidine have been shown in mice to protect against CIN presumably by decreasing regional vascular resistance with increased medullary blood flow [42]. In a randomized prospective double-blinded study of 60 children undergoing cardiac angiography, CIN occurred in only 10% of children who received dexmedetomidine compared to 37% of the controls [19]. The beneficial effect of dexmedetomidine may be due to its preventive effect on the release of vasoconstrictor agents such as endothelin and renin but since this study was restricted to low-risk patients, the results cannot be generalized.…”
Section: Alpha-2-receptor Agonistsmentioning
confidence: 99%